Recognizing Code Switching and Code Mixing in Talk Show Catatan Najwa with Maudy Ayunda on Youtube - Sulhizah Wulan Sari; Paramita Kusumawardhani (International Journal of English and Applied Linguistics (IJEAL), 2021)
People capable of speaking and writing two languages well are called bilingual. In contrast, the people who use two words or even in a sentence without paraphrase mean code-mixing. The purpose of this study is to know the types of code-switching and code-mixing. Code-switching and code-mixing are parts of sociolinguistics. Sociolinguistics studies an analysis of language. The linguistic factors are related to the factors beyond the language, such as language use done by its speakers in a particular speech community. Code-switching and code-mixing usually happened when talking to someone. The source of the research was the talk show Catatan Najwa with Maudy Ayunda on Najwa Shihab’s Channel Youtube. In this talk show, there was a guest star called Maudy Ayunda. She has just recently graduated from Oxford University and had a conversation with Najwa Shihab. The conversation happened on Najwa Shibah’s Youtube Channel. In this conversation, they used two languages that are Indonesian and English. This research used the qualitative descriptive method. To complete the data, The researcher also conducted library research. This study focused on video Najwa Shihab’s Channel Youtube. The research results are Inter-Sentential with 9 data as the code-switching type and Insertion with 7 data as the code-mixing type.